Use of hyaluronic acid preparations for treatment of osteoarthritis of major ligaments - Kalashnikov , Oleksiy; Sulyma, Oleksiy; Osadchuk , Taras; Zayets , Volodymyr; Nizalov , Taras; Kozak , Roman; Chernyak , Pavlo (Pain medicine, 2021)
The authors of the article analyzed the experience of domestic and foreign experts in the effectiveness of the use of HA preparations in the treatment of osteoarthritis of major ligaments. Background and Objective. To analyze the literature sources in order to determine the effectiveness of the use of HA preparations in the treatment of osteoarthritis of major ligaments. Materials and methods. Articles in specialized scientific journals and collections, Internet resource. Results. The analysis of literature sources determined the important role of HA preparations in the supplying and functioning of the articular cartilage. Researchers are inclined to believe that the ideal HA preparation should be as close as possible to the physiological HA of the synovial fluid of the joint. The developed domestic drug Arthro-Patch fully corresponds to these parameters. Conclusions. The use of modern injectable HA preparations is advisable at stages 1–3 of OA. Anti-inflammatory effect of HA preparations makes it possible to reduce the dose and time of administration of non-steroidal anti-inflammatory drugs and, as a consequence, reduce the risk of developing many adverse side effects of NSAIDs. The high level of safety of HA preparations, the absence of serious side effects during their long-term use determine their widespread use in the clinical practice of modern orthopedists.